The New Zealand soldier in World War II : myth and reality : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - McLeod, John Reginald (Massey University, 1980)
The New Zealand soldier has gained a reputation for being an outstanding soldier. The prolific New Zealand involvement in the numerous wars of this century have allowed him to develop and consolidate this reputation. World War II was to add further lustre to this reputation. The question that this poses is whether the reputation is justified – how much is myth and how much is reality? In the early stages of World War II the New Zealander failed to live up to his mythical reputation. The battles of Greece and Crete, in particular, showed the totally unprofessional nature of the New Zealand Army. Much of the weaknesses shown in these battles were caused by inadequate preparation. The Army had been one of the principal victims of the retrenchment policies of successive governments between the wars. In 1939 the New Zealand Army was in no state to fight a war. The Regular Force numbered no more than 500 and of the 10,000 Territorials only twenty percent could have been considered active. The Army was deficient not only in trained manpower but also in modern equipment. It was therefore a race against time to prepare the New Zealand Division for combat. Though the early years of the war demonstrated just how inadequate the preparations had been, the quality of the New Zealand soldier and the New Zealand Division increased. This was due to experience, improved logistics, and more competent leadership. Leadership was perhaps the major problem for the New Zealand Division in its early years. The failure of leadership is clearly illustrated by the loss of Maleme aerodrome and consequently Crete. The skills required for peacetime promotion as usual differed from those needed for leadership in war. As the war progressed promotion became based on ability and officers lacking in leadership skills were gradually replaced. The New Zealand Division had achieved a high standard by the end of the North African campaign but its standard was not at variance with other Divisions with similar experiences. Battles such as Minqar Qaim, El Alamein, Tebaga Gap and Takrouna were examples of the Division profiting from its experiences. However, there were still problems. At Takrouna the New Zealanders were able to bring all their experience to bear, but the need for new tactics in this unusual attack found the New Zealanders a little lacking, and another lesson was learnt. The New Zealand soldier is not physically or mentally superior to any other soldier. The Division did have advantages such as Freyberg's Charter and the national nature of the Division and this helped the soldiers and the Division in their battles. What counts though, for fighting ability in training, experience, leadership and logistics. In all armies and all Divisions these fluctuate and correspondingly so does the fighting ability of that Division. The myth of the Mew Zealand soldier has developed as New Zealanders search for a national identity. The myth has grown with New Zealand nationalism to a stage where New Zealanders are unable to distinguish myth from reality.
Keywords: World War Two; New Zealand soldiers; Second World War; New Zealand army